Fungsi Pengawasan dalam Pendidikan Islam (Indo-MathEdu Intellectuals Journal, 2025)
Supervision is the action or process of controlling, assessing, and determining deviations in the implementation of work in accordance with predetermined plans and standards. In Islam, supervision is not only carried out by humans but also by God who creates, so it is required to do in accordance with what has been planned in the organization so that what is a common goal is achieved. This study aims to determine the role of the supervisory function in Islamic education. The type of research used is field research. The data collection technique uses field observation, interview, and documentation methods. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the analysis show that supervision in Islam is carried out to correct what is not good or wrong and correct the wrong and justify the right. Supervision in Islam comes from monotheism and faith in Allah SWT. The person who has faith is sure that Allah must be watching over His servant, so he will act carefully. Supervisors must prioritize their professional principles, including: Tawhid, amanah, istiqamah, having knowledge, and tabliq